Achieving High Fill Factor via Increasing Interfacial Disorder to Inhibit Bimolecular Recombination for Efficient Organic Solar Cells - He, Dan; Xie, Linwei; Bai, Yahui; Zhang, Huotian; Liu, Liping; Kong, Jingyao; Chai, Yongqiang; Li, Xiaojun; Wang, Mengni; Zhang, Yajie; Zhang, Jianqi; Li, Yongfang; et al. (Angewandte Chemie International Edition, 2025)
The inferior fill factor (FF) is one of main reasons impeding further improvement of power conversion efficiencies (PCEs) in organic solar cells (OSCs). But no theoretical framework for high FFs has been established yet. Herein, an efficient strategy is developed to enhance FFs via introducing a small molecule, CNDT, into active layer to increase electron donor/acceptor interface disorder, raise energy barrier for charge back transfer, and thus reduce bimolecular recombination rate constant (krec). CNDTs tend to distribute over donor/acceptor interfaces and disturb molecular stacking of Y6 to deliver more disordered donor/acceptor interfaces but higher crystal quality in the D18:Y6+ blend film, compared to D18:Y6. Altogether, in the D18:Y6+ blend film, a higher energy of charge transfer state magnifies energy barrier for charge recombination to decrease charge recombination rate/ratio and reduce krec, inhibiting bimolecular recombination in devices. Therefore, FFs of OSCs are improved from 75.78% (D18:Y6) to 81.13% (D18:Y6+), yielding a higher PCE of 19.45%. Moreover, D18:L8-BO+ based OSCs feature FFs over 83%, a record for OSCs so far. PCE increases subsequently to 19.80%. It demonstrates that increasing interface disorder without sacrificing crystal quality enhances energy barrier of charge recombination and inhibits bimolecular recombination to efficiently improve FFs for higher PCEs.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Charge carrier recombination; Donor/acceptor interfaces; Fill factors; Organic solar cells

A novel empirical method for quickly estimating the charge-transfer state of fullerene-donor derivatives - Liu, Liping (Physical Chemistry Chemical Physics, 2019)

Cyano-Functionalized Graphitic Carbon Nitride with Adsorption and Photoreduction Isosite Achieving Efficient Uranium Extraction from Seawater - Liu, Liping (Advanced Functional Materials, 2024)

Dual Function of Naphthalenediimide Supramolecular Photocatalyst with Giant Internal Electric Field for Efficient Hydrogen and Oxygen Evolution - Liu, Liping (Small, 2024)

Efficient Photocatalytic Hydrogen and Oxygen Evolution by Side-Group Engineered Benzodiimidazole Oligomers with Strong Built-in Electric Fields and Short-Range Crystallinity - Liu, Liping (Angewandte Chemie International Edition, 2022)

Electron-enriched supramolecular PDI-SiO2 promoting PDS activation for enhanced photocatalytic advanced oxidation - Liu, Liping (Applied Catalysis B-Environmental, 2024)

Enhanced internal electric field of CdS/NU-M Z-scheme heterojunction for efficient photocatalytic hydrogen evolution - Liu, Liping (Chemical Engineering Journal, 2024)

Enhancing Carrier Transport via σ-Linkage Length Modulation in D-σ-A Semiconductors for Photocatalytic Oxidation - Liu, Liping (Angewandte Chemie International Edition, 2023)

Enhancing internal electric field of 3D porous chitosan-PDI polymer with donor-acceptor structure for efficient photocatalytic advanced oxidation - Liu, Liping (Applied Catalysis B-Environmental, 2024)

Hierarchically nanostructured MnCo2O4 as active catalysts for the synthesis of N-benzylideneaniline from benzyl alcohol and aniline - Liu, Liping (Green Chemistry, 2017)

Highly efficient photocatalytic hydrogen production via porphyrin-fullerene supramolecular photocatalyst with donor-acceptor structure - Liu, Liping (Chemical Engineering Journal, 2022)

In Situ Switching of Photoinduced Electron Transfer Direction by Regulating the Redox State in Fullerene-Based Dyads - Liu, Liping (Journal of the American Chemical Society, 2020)

One-pot solvothermal synthesis of magnetically separable rGO/MnFe2O4 hybrids as efficient photocatalysts for degradation of MB under visible light - Liu, Liping (Materials Chemistry and Physics, 2019)

Optimizing electronic synergy of atomically dispersed dual-metal Ni–N4 and Fe–N4 sites with adjacent Fe nanoclusters for high-efficiency oxygen electrocatalysis - Liu, Liping (Energy and Environmental Science, 2024)

Surface modification of TiO2 nanosheets with fullerene and zinc-phthalocyanine for enhanced photocatalytic reduction under solar-light irradiation - Liu, Liping (Science China Materials, 2020)

The Transfer Dehydrogenation Method Enables a Family of High Crystalline Benzimidazole-linked Cu (II)-phthalocyanine-based Covalent Organic Frameworks Films - Liu, Liping (Angewandte Chemie International Edition, 2024)